2014
DOI: 10.1097/rct.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

CT Findings in Temporal Bone Osteoradionecrosis

Abstract: Purpose The goal of this study is to describe CT findings in patients with clinically proven temporal bone osteoradionecrosis (TB-ORN). Methods and materials CT scans of twenty patients were retrospectively evaluated for bony and soft tissue abnormalities. Clinical severity was graded based on level of therapy administered: mild (observation), moderate (antibiotics/hyperbaric oxygen), or severe (surgery). Results Radiation dose to the primary tumor ranged from 30 to 75.6 Gy. Time to onset of ORN from compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The differential diagnosis for the radiological findings of bilateral otic capsule demineralisation includes osteogenesis imperfecta, otosclerosis, and Paget's disease [30]. Radiation related change is another increasingly recognised cause of temporal bone demineralisation [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnosis for the radiological findings of bilateral otic capsule demineralisation includes osteogenesis imperfecta, otosclerosis, and Paget's disease [30]. Radiation related change is another increasingly recognised cause of temporal bone demineralisation [31].…”
Section: Discussionmentioning
confidence: 99%
“…The temporal bone is frequently included within the radiation field during the treatment of head and neck cancer. Clinical symptoms can present 3 months to 40 years from the date of the initial treatment [31]. The pathophysiology involves an oblierative endarteritis and periarteritis which causes avascular necrosis [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an open wound is then secondarily exposed to skin flora leading to an osteomyelitis clinical scenario. Studies have shown the onset of osteoradionecrosis varied from 1 to 22 years with a mean of 8 years [44,45]. CT findings identified erosions of the external auditory canal and mastoid effusions in nearly all patients.…”
Section: Osteonecrosis/osteomyelitis Of Temporal Bonementioning
confidence: 99%
“…Other CT features included soft tissue enhancement mimicking tumor recurrence, and soft tissue air/abscess formation. The TMJ may also be involved with erosions of the condylar bone concurrently present with temporal bone osteoradionecrosis [45]. In cases where osteonecrosis is identified in the absence of prior radiation therapy, medication-related osteonecrosis may be a consideration but requires clinical correlation to identify a prior history of anti-resorptive type medications such as bisphosphonates and/or denosumab.…”
Section: Osteonecrosis/osteomyelitis Of Temporal Bonementioning
confidence: 99%